Subunit III of cytochrome c oxidase is not involved in proton translocation: a site-directed mutagenesis study. - Haltia, T (1991)
Subunit III (COIII) is one of the three core subunits of the aa3-type cytochrome c oxidase. COIII does not contain any of the redox centres and can be removed from the purified enzyme but has a function during biosynthesis of the enzyme. Dicyclohexyl carbodiimide (DCCD) modifies a conserved glutamic acid residue in COIII and abolishes the proton translocation activity of the enzyme. In this study, the invariant carboxylic acids E98 (the DCCD-binding glutamic acid) and D259 of COIII were changed by site-directed mutagenesis to study their role in proton pumping. Spectroscopy and activity measurements show that a structurally normal enzyme, which is active in electron transfer, is formed in the presence of the mutagenized COIII. Experiments with bacterial spheroplasts indicate that the mutant oxidases are fully competent in proton translocation. In the absence of the COIII gene, only a fraction of the oxidase is assembled into an enzyme with low but significant activity. This residual activity is also coupled to proton translocation. We conclude that, in contrast to numerous earlier suggestions, COIII is not an essential element of the proton pump.